Egyptian Liver Journal - Abdel Ghaffar, Tawhida; El-Azab, Gasser; Allam, Naglaa; Rashad, Mona.; El Folly, Runia; Abdelsameea, Eman.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
As a highly respected journal in the Middle East, the Egyptian Liver Journal (EGLJ) is a peer-reviewed clinical journal, formally published by the Society of Friends of Liver Patients in the Arab World (SLPAW) and the National Liver Institute, Menoufia University (NLI). The scope of the journal covers all the latest issues relating to hepatobiliary surgery, pediatric hepatology, clinical pathology, virology, microbiology, epidemiology and histopathology. The journal also aims to include clinical and basic research in both humans and experimental models in the fields of hepatology.
Keywords: Internal medicine; Liver; Physiology; Virology; Epidemiology; Medical care; Internal Medicine; Hepatic Physiology; Virology; Epidemiology; Health Care